Good Knowledge and Attitude can Improve Nurse Compliance in Performing Wound Care Actions Using Moist Wound Healing Method in Accordance with Standard Operating Procedures (SOP) - Mardiati Barus; Imelda Derang; Melina Cecilia Tarigan (Media Keperawatan Indonesia, 2022)
Moist wound healing is a method of treating moist and closed wounds to accelerate the healing process, the growth of new tissue and prevent infection. The survey results found that respondents know moist wound care 66.7%, rarely use the moist method of 53.4%, and use conventional techniques of 73.3%, therefore it takes knowledge, attitude, and a lot of experience to be able to achieve maximum wound care. This study aims to determine the relationship between knowledge and attitudes with the actions of nurses on wound care using the moist wound healing method at RSUP H. Adam Malik Medan in 2021. The study was an analytic observational study with a cross-sectional design. The total population in the study was the same as the total sample size of 62 respondents who were obtained using the total sampling technique in-room RB 2B, RB 3, and the Burn Unit. The results showed that good knowledge was 66.1%, a positive attitude was 82.3%, and taking action according to the SOP was 83.9%. Based on the Fisher exact test, it was obtained a p-value for knowledge, and attitudes of 0.001 (p <0.05), which means that there is a relationship between knowledge, attitudes, and actions of nurses regarding wound care using moist wound healing method. It is hoped that the nurses can increase their knowledge and experience to create a positive attitude in carrying out wound care using the moist wound healing method to accelerate the healing of patients.